(untitled) (Journal of Rangpur Medical College, 2022)
Background: Risk stratification is an essential and first component of the pre-Ramadan assessment of patients with diabetes mellitus (DM) who wish to fast. Limited data are reported from Bangladesh regarding risk stratification of people with DM who wish to fast. Objective: To determine the risk status of people with DM who wish to fast during Ramadan. Methods: This cross-sectional observational study was done among Muslim people of DM with at least one year of experience of Ramadan in previous years after their diagnosis. Along with baseline characteristics, the individual 14 risk elements of the International Diabetes Federation and Diabetes & Ramadan International Alliance (IDF-DAR) risk calculator- 2021 were assessed. Patients were categorized into low, moderate, and high risk with a total score of 0-3, 3.5-6, and ≥6.5 respectively. Moderate and high-risk patients were counseled about their risk of fasting and requested to reconsider their wishes. Results: Among 569 participants, (mean age 50.97±12.02 years, male-female ratio 36.2:63.8) 37.8%, 38.8%, and 23.4% had high, moderate, and low risk respectively. Risk scores were significantly higher in older age (p<0.001), male sex (p=0.024), residence in Chattagram than Rajshahi division (p=0.009) as well as housewife and businessman than other occupations (p=0.012). Despite knowing the risks of fasting, 88.8% of people with high risk and 96.8% of people with moderate risks still wished to fast. The people who still wished to fast despite knowing their risks of fasting had significantly lower percent of macrovascular disease (p=0.039), lower creatinine levels (p<0.001), with a lower percent of dipstick proteinuria (p=0.010), and use of insulin (p=0.021) than those who changed their decision. Conclusions: Nearly 90% of persons with DM with moderate/high risk for fasting still wished to fast despite their exemption. These at-risk population needs guidance, monitoring, and follow-up for safe fasting. J Rang Med Col. September 2022; Vol. 7, No. 2:4-11